HUMAN TRAFFICKING AS A THREAT TO MARITIME SECURITY AND THE ROLE OF HUMAN FACTORS IN ITS MANAGEMENT - Milkov, Todor (E-Journal VFU, 2024)
This article examines such a topical issue, namely - human trafficking as a threat to national maritime security and the role of the human factor in its accurate management. Indications of traffic and its manifestations are shown, as well as the role and place of the human factor in managing this security and ensuring the safety of our maritime borders. The issue is complex and cumulative, and the relationship between human trafficking and the human factor in ensuring the safety of our maritime borders is proportional. Certain strategic areas and specifics are being studied, which have their inevitable practical-applied impact on the national maritime security and safety systems.
Keywords: Traffic; People; Threat; Human Factors; Maritime Security; Safety; State Borders; Systems; Assessment; Interaction